Radiological Protection of the Environment and its Implementation into IAEA Safety Standards - D. Telleria; G. Proehl (PPIKSN-BATAN, 2013)
Radiological protection of the environment has been intensively discussed in recent years. Much progress has been made recently with regard to the development of models: (i) to estimate the uptake of radionuclides by flora and fauna in different habitats and ecosystems; (ii) to calculate internal and external exposures for a wide range of terrestrial and aquatic organisms; and (iii) in investigating and analyzing the effects of radiation exposures to biota. This paper gives an overview of the current status of this work. Furthermore, the current status of the integration of environmental protection into the radiation protection system is also summarized.Received: 8 November 2013; Revised: 23 December 2013; Accepted: 30 December 2013